On reliability analysis in priority standby redundant systems based on maximum entropy principle. Issue 1 (2nd January 2021) - Hirata, Ryosuke; Arizono, Ikuo; Takemoto, Yasuhiko
ABSTRACT: There are many studies on standby redundant systems, since those are the most standard models for ensuring reliability in systems. Particularly, two-component priority standby redundant systems are one of the most fundamental and important redundant models in the reliability theory. In recent years, the procedure for evaluating the mean time to failure (MTTF) of the two-component priority standby redundant system has been proposed by using mixed Erlang distributions as approximate distributions. In this study, by expanding the idea on evaluating MTTF proposed in the previous research, an evaluation method for the variance of failure times (VOFT) in the two-component priority standby redundant system has been presented. Furthermore, we have proposed a procedure for deriving the reliability function in the system based on the maximum entropy principle by utilizing MTTF and VOFT. Through some numerical applications, the validity of the procedures for deriving the reliability function developed in this study has been shown.